Acquired Thrombocytopenia in Contemporary Transcatheter Aortic Valve Prosthesis - Petrov, Asen; Taghizadeh-Waghefi, Ali; Diab, Abdel-Hannan; Breuer, Linda; Arzt, Sebastian; Matschke, Klaus Ehrhard; Alexiou, Konstantin (The Thoracic and Cardiovascular Surgeon, 2023)
Background Postprocedural thrombocytopenia is a known phenomenon following transcatheter aortic valve implantation (TAVI). The aim of this study is to evaluate whether postinterventional platelet kinetics differ when comparing the current generation of balloon-expandable valve (BEV) and self-expanding valve (SEV) prostheses.Methods We performed a retrospective analysis of patients undergoing TAVI at our facility between 2017 and 2019. Patients were stratified according to the type of prosthesis used: BEV or SEV. Hematocrit-corrected platelet counts were calculated to account for dilution. Nadir platelet counts (lowest recorded platelet count), drop platelet counts (DPC; highest relative platelet drop from baseline), and severity of thrombocytopenia during the discourse and at discharge were assessed.Results Of the 277 included patients, 212 received SEV and 65 BEV. BEV patients were younger (81.8 ± 4.4 years vs 79.7 ± 6.8 years, p = 0.03). Further demographic characteristics were similar between groups. Implanted SEV were larger (p < 0.001) and had shorter procedural times (p < 0.01). There were no significant differences in postprocedural discourse. Postinterventional platelet drop was more pronounced in BEV patients in several evaluated metrics: mean DPC (24.3 ± 10.9% vs 18.8 ± 14.8%, p < 0.01), patients with DPC > 30% (n = 19, 29.2%, vs n = 33, 15.6%, p = 0.02), and also when comparing platelet kinetics.Conclusion Despite improvements in outcome, the current generation of balloon-expandable TAVI prostheses carries a predisposition for postprocedural thrombocytopenia even when the effects of dilution are accounted for.
Keywords: aortic valve and root; heart valve; transapical; percutaneous (TAVI); surgery; complications